Measurement of metric and nonmetric parameters for determining the gender of the human mandible - Anil Kumar; Penprapa S Klinkhachorn; Ciraj Ali Mohammed (Wolters Kluwer Medknow Publications, 2022)
Background: In humans, the mandible is the longest, densest, and most robust facial bone. It displays a high degree of phenotypic variation between sexes and is resistant to postmortem trauma. Measures of male and female mandibles were quantified in this study along with nonmetric and metric parameters to determine the gender. Methodology: In this retrospective observational study, 96 mandibles (55 males and 41 females) were evaluated for gender through the measurement of 15 metric and 5 nonmetric parameters. Results: A significant correlation between nonmetric variables of the squared chin (85.54%), prominent muscle markings (74.54%), everted gonial flares (94.54%), and triangular coronoid processes (81.81%) was found. Females, by contrast, tended to have a rounded chin (68.49%), a less prominent muscle marking (53.6%), an inverted gonial flare (95.54%), and a hooked shape coronoid process (80.48%). All metric mandible parameters were determined, evaluated, and statistically analyzed in SPSS to determine whether gender had a relationship with the mandibles. Conclusion: Various metric and nonmetric criteria, in addition to existing methods, can be used to determine the gender of a person's mandible.